Incentivising structural reforms in Europe? A blueprint for the European Commission's Reform Support Programme - Mathias Dolls; Clemens Fuest; Carla Krolage; Florian Neumeier; Daniel Stöhlker (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
This paper contributes to the current debate how a faster implementation of structural reforms fostering the process of economic convergence in Europe can be achieved. We discuss the rationale and potential adverse effects of providing financial incentives for structural reforms. After a discussion of the European Commission's proposal of the `reform support programme', we present our proposal of `national convergence roadmaps' which deviates from the Commission proposal in some key dimensions. Our proposal of national convergence roadmaps reflects the fact that ensuring progress towards convergence targets is primarily a responsibility of the individual member states, not of the EU or European institutions and bodies like the European Commission and the Eurogroup.
Keywords: 330